Evaluating the safety of perioperative dexamethasone treatment: A retrospective analysis of a single center pediatric low‐grade glioma cohort. Issue 9 (23rd December 2022) - Gorodezki, David; Zipfel, Julian; Queudeville, Manon; Holzer, Ursula; Bevot, Andrea; Schittenhelm, Jens; Nägele, Thomas; Schuhmann, Martin U.; Ebinger, Martin
Abstract: In addition to surgical management, corticosteroids have proven to be beneficial in the management of acute symptoms related to CNS tumors, and have been widely used for many decades, with dexamethasone (DM) representing the most commonly used agent. However, lately published in vitro data possibly indicates a DM‐induced suppression of oncogene‐induced senescence (OIS) in a preclinical pediatric low‐grade glioma (pLGG) model, which, alongside data associating perioperative DM treatment with reduced event‐free survival in adult glioma, raises questions concerning the safety of DM treatment in pLGG. A total of 172 patients with pLGG were retrospectively analyzed concerning the impact of perioperative DM application on postoperative short‐ and long‐term tumor growth velocity and progression‐free survival (PFS). Three‐dimensional volumetric analyses of sequential MRI follow‐up examinations were used for assessment of tumor growth behavior. Mean follow‐up period accounted for 60.1 months. Sixty‐five patients (45%) were perioperatively treated with DM in commonly used doses. Five‐year PFS accounted for 93% following gross‐total resection (GTR) and 57% post incomplete resection (IR). Comparison of short‐ and long‐term postoperative tumor growth rates in patients with vs without perioperative DM application showed no significant difference (short‐term: 0.022 vs 0.023 cm 3 /month, respectively; long‐term: 0.019 vs 0.023 cm 3 /month, respectively). Comparison of PFS post IR (5‐year‐PFS: 65% vs 55%, respectively; 10‐year‐PFS: 52% vs 53%, respectively) and GTR (5‐ and 10‐years‐PFS: 91% vs 92%, respectively) likewise showed similarity. This data emphasizes the safety of perioperative DM application in pLGG, adding further evidence for decision making and requested future guidelines. Abstract : What's new? Dexamethasone is widely used in symptom management for central nervous system (CNS) tumors. Perioperative dexamethasone therapy, however, is associated with reduced event‐free survival in adult glioma, and recent preclinical findings indicate that dexamethasone suppresses senescence in pediatric low‐grade glioma. Here, in a pediatric low‐grade glioma cohort, no significant difference was observed in tumor growth rates or in progression‐free survival in patients treated with or without perioperative dexamethasone. Survival following gross total or incomplete resection was also similar. The findings support the use of perioperative dexamethasone therapy in pediatric patients with low‐grade glioma.